Analysis of Factors Affecting Risk Management Disclosure: (Empirical Study on Food and Beverage Sub-Sector Manufacturing Companies on the Indonesia Stock Exchange Periode 2017-2020) - Dara Rahma Septia; Melly Juwita Nasution; Nunik Nurmala Wardani; Rafif Sultan Naufal (CV. Ulil Albab Corp, 2023)
Risk management disclosure is very important in decision making for both companies and investors. The risks faced by companies in running their business need to be managed through risk management, so that risk disclosure plays an important role. This study aims to analyze the factors that influence risk management disclosure in food and beverage sub-sector manufacturing companies listed on the Indonesian stock exchange in 2017-2020. The sampling method used was purposive sampling. The analysis technique used is panel data regression analysis. The number of samples used in the study were 19 companies. The results of this research show that Leverage, Profitability, and Company Size simultaneously affectrisk management disclosure. Partially, Leverage has no effect on risk management disclosure. While Profitability and Company Size have an effect on risk management disclosure.